WAYS TO PRESERVE OVARIAN RESERVE IN WOMEN DURING CYTOSTATIC THERAPY OF MALIGNANT LYMPHOMAS - Liana Elgudgaevna Kokaeva; Evgeniya Borisovna Troik (Вестник Северо-Кавказского федерального университета)
In a review of the literature from the modern point of view, the effect of chemotherapy on women's reproductive health and ways to minimize long-term side effects of the specific treatment of lymphomas.